Socialization on the Optimization of Digital Marketing for Student Activity Information at SMK Tunas Karya - Tantri Hidayati Sinaga; Hasdiana; Sembiring, Boni Oktaviana; Eka Rahayu; Arie Rafika Dewi; Marina Elsera (Jurnal Pengabdian Masyarakat Berdampak, 2026)
The use of social media at SMK Swasta Tunas Karya is still not optimal, particularly in delivering student activity information in a structured and appealing manner. Students have not yet developed sufficient understanding of digital marketing strategies and content management, resulting in school information being communicated less effectively. This Community Service Program (PkM) is intended to develop students’ abilities in utilizing social media, particularly Instagram, as a tool for sharing information and promoting the school. The activities were carried out through socialization and training provided to students of SMK Tunas Karya. The materials included basic digital marketing concepts, content planning, simple writing techniques, and hands-on practice in managing the school’s Instagram account. Through this practical approach, students gained direct experience in creating engaging content aligned with the school’s communication needs. The results show an improvement in students’ ability to create more interactive, creative, and relevant content. Students became capable of combining visual elements, text, and effective information presentation styles to publish school activities. This program also contributed to increasing students’ soft and hard skills in digital creativity, media literacy, and online platform management. With these improved skills, the school benefits from more efficient information dissemination and strengthened branding as an institution that adapts to technological developments.